A STUDY OF THE QUALITATIVE CHARACTERISTICS AND CONCENTRATIONS OF SOME ACTIVE COMPOUNDS IN FENUGREEK SEEDS UNDER THE INFLUENCE OF SPRAYING PLANTS WITH CYTOKININS AND LICORICE EXTRACT - D. M. Ahmed; U. H. Mheidi (مجلة الأنبار للعلوم الزراعية)
A field experiment was carried out during the winter season 2021-2022 in Anbar Governorate in the Al-Saqlawiya region located on the banks of the Euphrates River to study the effect of cytokinins and licorice extract on some active compounds of fenugreek seeds. The experiment included the use of four concentrations of cytokinins (225, 150, 75, 0). L-1 mg, which was in the main plots, and four concentrations of licorice extract (30, 20, 10, 0) g L-1 were used, which occupied the sub-plot panels of the experiment. The results showed that the concentration of 225 mg L-1 was significantly higher than cytokinin in traits. Quality (protein percentage and carbohydrate percentage in seeds). While the concentration exceeds 30 gm. L-1 was significantly increased from licorice extract in qualitative traits, so the percentage of protein was 27.48 and the percentage of carbohydrates in seeds 10.31. Licorice root has the highest rates in the qualitative traits, and the results also showed an increase in the percentage of active compounds diagnosed by the HPLC technology, where the concentration of 225 mg L-1 of cytokinin gave the highest rate of scopolinin 54.96 mg L-1, choline 88.9 mg L-1 and yamogenin 94.4 mg L-1 and diosgenin 266.0 mg L-1 except for trigonelline.